Pengaruh Variabel Risk Tolerance Dan Overconfidence Terhadap Pengambilan Keputusan Investasi - Dwi Astutik; Mohammad Hidayatul Holili; Susilo Adi; Didik Sofian Haryadi; Heni Dwi Listyaningrum; Henny Kumalasari Widodo (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
Where There Are Differences in the Influence of Overconfidence and Risk Tolerance on Making Investment Decisions. Where this research will carry out tests and carry out analyzes on Risk Tolerance and also Overconfidence in making decisions regarding Investment. In the research conducted by the author to determine the influence of Overconfidence and Risk Tolerance on Making Investment Decisions. This research uses data in the form of numbers. According to Sujarweni, quantitative data is data in the form of numbers. Based on the results after testing, Risk Tolerance and Overconfidence have a significant effect on Investment Decision Making.